Analysis of multiple cosmogenic nuclides constrains Laurentide Ice Sheet history and process on Mt. Mansfield, Vermont's highest peak. (1st February 2019) - Corbett, Lee B.; Bierman, Paul R.; Wright, Stephen F.; Shakun, Jeremy D.; Davis, P. Thompson; Goehring, Brent M.; Halsted, Christopher T.; Koester, Alexandria J.; Caffee, Marc W.; Zimmerman, Susan R.
Abstract: Constraining glacial history and process on Mt Mansfield, the highest peak in Vermont (1339 m a.s.l.), provides insight into how the Laurentide Ice Sheet shaped the underlying landscape, when latest Pleistocene ice retreated, and how upland and lowland glacial histories relate. Here, we quantify in situ cosmogenic 10 Be in 20 bedrock and boulder surfaces, as well as in situ cosmogenic 14 C in three of those surfaces, to assess subglacial erosion and exposure history. Isotopic concentrations indicate that Mt. Mansfield's lower elevations (∼400–1200 m a.s.l.) were deeply eroded by at least several meters during the last glaciation and then deglaciated rapidly; 10 Be ages across this elevation span are indistinguishable and average 13.9 ± 0.6 ka (n = 15), suggesting that 800 m of ice thinning occurred within at most about a millennium. Conversely, the higher elevations (>1200 m a.s.l.) preserve a more complex geomorphic history. Mt. Mansfield's summit surfaces contain 10 Be from previous periods of exposure, indicating that the mountaintop landscapes were likely preserved beneath cold-based, weakly-erosive glacial ice. Exposure ages from the shorter-lived isotope, 14 C, are younger (9.7 and 11.7 ka), suggesting that Mt. Mansfield's summit was covered until the early Holocene, perhaps by snowfields, ice carapaces, and/or till. Our findings, in context of previous work, suggest that thinning Laurentide ice flowed through the valleys for at most hundreds of years following deglaciation of the uplands, but that the summit remained shielded by ice or sediment for millennia after the valleys became ice-free. Highlights: We use cosmogenic nuclides to constrain Laurentide Ice Sheet history and behavior. Mt. Mansfield, the highest point in Vermont, was deglaciated rapidly ∼13.9 ka. The lower elevations (<1200 m a.s.l.) were deeply eroded by flowing ice. The summit area was covered by cold-based ice and was minimally eroded.